Screening of Methanolic Bark Extract of Albizia odoratissima for Antimicrobial Activity - Kumar, Dinesh; Kohli, Sonia; Kumar, Sunil; Gupta, Jyoti; Jain, Pranay; Kumar Pundir, Ram (Pharmacognosy Communications)
Introduction: Albizia odoratissima Benth., [Family: Mimosaceae] is commonly known as Black Siris. In traditional Indian Medicine, bark of A. odoratissima is used in the treatment of leprosy, ulcers and cough. The objective of this study was to screen methanolic extract of A. odoratissima bark for antimicrobial activity owing to its ethnomedicinal use. Method: In agar well diffusion method, plate count agar (PCA) plates were inoculated with 100µl of each pathogenic microorganism adjusted to standardized inoculum (1.5 × 108 CFU/ml) in triplicates and spread with sterile swabs. After incubation for 24 hrs at 37 °C, the plates were observed. The zone of inhibition was measured and expressed in millimeters. Result and Discussion: The extract showed good antibacterial activity only against Gram positive bacteria with zone of inhibition ranging from 12 mm to 21 mm. Maximum zone of inhibition of 21 mm at 80 µg/ml concentration was observed against S. mutans. The extract did not show any inhibitory activity against Gram-negative bacterium (P. auriginosa). The test antibiotic ciprofloxacin showed activity with zone of inhibition ranging from 29 mm to 34 mm while ketoconazole showed zone of inhibition of 28 mm against C. albicans. Phytochemical analysis of the extract showed the presence of steroids, tannins, phenolics, saponins. Conclusion: From the study, it can be concluded that the methanolic extract of A. odoratissima bark possesses significant antimicrobial activity against Gram positive bacteria (Staphylococcus aureus, Staphylococcus mutans) and yeast (Candida albicans) which might be due to the presence of steroids, saponins and phenolics in the bark, with no effect on Gram negative bacteria.
Keywords: Albizia odoratissima; Diffusion; Folk; Incubation; Pathogenic